2018
DOI: 10.1111/all.13482
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of viral hepatitis and chronic spontaneous urticaria: A systematic review

Abstract: Chronic viral infections including those by hepatitis B (CHB) virus and hepatitis C (CHC) virus have been reported to be comorbidities of chronic spontaneous urticaria (CSU). Here, we performed the first comprehensive review of the peer-reviewed literature (PubMed, Web of Science and Google Scholar) on the prevalence of CHB and CHC in patients with CSU and vice versa. The prevalence of CHB and CHC in CSU does not appear to be increased. Less than 5% and 2% of patients with CSU have markers of CHB and CHC, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
(100 reference statements)
1
16
0
1
Order By: Relevance
“…It is indicated that there is an increased risk of developing acute urticaria and CU, particularly in female patients [48 ]. A comprehensive literature review indicated that chronic hepatitis B and C are not associated with CSU and so routine screening for these viral infections in CSU patients is not necessary [49 ].…”
Section: Multimorbiditiesmentioning
confidence: 99%
“…It is indicated that there is an increased risk of developing acute urticaria and CU, particularly in female patients [48 ]. A comprehensive literature review indicated that chronic hepatitis B and C are not associated with CSU and so routine screening for these viral infections in CSU patients is not necessary [49 ].…”
Section: Multimorbiditiesmentioning
confidence: 99%
“…Infection with viral hepatitis has also been associated with CSU 16, 17 and guidelines suggest performing a hepatitis screen if transaminases are abnormal 1 . However, a systematic review on the subject revealed that the prevalence of hepatitis B and hepatitis C was no greater in CSU patients than compared with the general population 18 .…”
Section: Discussionmentioning
confidence: 97%
“…There are other examples in the literature where chronic infection has been linked with CSU, and one such example is HepC and HepB. However, a comprehensive review of the literature failed to find an obvious associations, and routine screening is not recommended 2 .…”
mentioning
confidence: 99%
“…22 Also identified is hepatitis, pathogens as strongyloides stercoralis, or helicobacter pylori to mention a few. 24,32 In the laboratory evaluation of urticaria, serum IgE levels, complete blood counts (hypereosinophilia, basophilia), hepatitis screen (HBVand HCV) and stool ova/parasite tests are done. 2 Sr IgE, was raised in almost half the patients in whom it was done.…”
Section: Discussionmentioning
confidence: 99%
“…13,[21][22][23] In a large proportion of patients triggers are not identifiable. 14 In the few patients where triggers have been identified, these triggers include alcohol, Hepatitis B Virus and Hepatitis C Virus infection, 2,24 drugs (non-steroidal anti-inflammatory drug) and stress. 14 Food has not been found to trigger urticaria despite patients giving a history of food as a trigger.…”
Section: Introductionmentioning
confidence: 99%